EFFECT OFFERMENTED PAPAYA LEAVESON ORGANOLEPTIC CHARACTERISTICS OF FEMALE BALI DUCKS AGE 10 WEEK - A. T., Pangestu; Siti, N. W.; Sukmawati, N. M. (Jurnal Peternakan Tropika, 2018)
The aim of this research is to know the effect of fermented papaya leaves in ration on organoleptic characteristics of female ducks. The study was conducted in Kediri, Tabanan-Bali. The design used was Completely Randomized Design (RAL) consisting of 3 treatments. The treatments were P0 (commercial ration without fermented papaya leaves), P1 (commercial ration + 5% fermented papaya leaves) and P2 (commercial ration + 10% fermented papaya leaves) and as replicates were 15 panelists determining preferred levels (hendonic scale), then transformed to a numerical value for statistical analysis. Assessment of the numbers 1 (one) to 5 (five) indicating the value (score) in the following order: 1 (very dislike), 2 (dislikes), 3 (regular), 4 (like), 5 (very like) The observed variables are color, aroma, flavor, texture and overall acceptance. The results showed that the addition of fermented papaya leaves in ration increased the texture value or significantly different (P <0.05). The results of color, flavor, taste and overall acceptance have no significant or different effect (P> 0.05) with controls, but as the addition of papaya leaf degree is favored, the panelist favorability tends to increase. Based on the results of this study it can be concluded that the addition of fermented papaya leaves at the level of 5% - 10% in the ration can increase the value of tenderness or texture of female duck meat, but it does not affect the color, aroma, flavor and overall acceptance. Keywords: organoleptic characteristics, fermented papaya leave , duck mea t